Analisis Daya Tarik Wisata, Kualitas Pelayanan Dimediasi Kepuasan Wisatawan dan Keterlibatan Wisatawan, pada Minat Berkunjung Ulang (Pengembangan Wisata Berkelanjutan di Pulau Padar - Nurbasari, Anny; Aribowo, Agus; Budiningsih, Tatik; Morgan, Gerry; Raihin, Yusuf Osman (Akademi Sekretari Manajemen Taruna Bakti, 2024)
This research aims to analyze the influence of tourist attractions and service quality on tourists' intention to visit again, with tourist satisfaction and tourist involvement as mediating variables. The research was conducted at the Pulu Padar tourist destination using quantitative methods by distributing questionnaires to 300 respondents using a non-probability sampling technique, namely a purposive sampling technique, including domestic and foreign visitors. Data collection through interviews, observations and distributing questionnaires using Google forms distributed via social media and direct surveys. Data processing and hypothesis testing uses the Structure Equation Modeling (SEM) method. The research results show that there is a positive influence of Destination Image on Tourist Satisfaction, Service Quality has a positive influence on Tourist Satisfaction, and there is no influence of Tourist Engagement. regarding Interest in Revisiting. Furthermore, destination image and service quality do not have a positive effect on intention to visit again, which is mediated by tourist satisfaction and tourist involvement. This research provides practical implications for managers of Padar Island tourist destinations, namely considering the diversification of products and experiences offered. This may include developing new attractions, cultural events or tour packages that appeal to different market segments.